Investigating Variable Speed Wind Turbine Transient Performance Considering Different Inverter Schemes and SDBR - Okedu, Kenneth E.; Barghash, Hind F. A. (Frontiers in Energy Research, 2021)
This paper investigates transient performance of variable speed wind turbine DFIG (Doubly Fed Induction Generator)-based taking into account different scheme configurations of the power converter system. The schemes investigated are a 2 level six step Insulated Gate Bipolar Transistor (IGBT) inverter, a parallel interleaved 2 level six step IGBT inverter, and 3-level IGBT inverter. All schemes were compared during severe three phase to ground fault at the terminal of the DFIG wind turbine using the conventional Phase Lock Loop (PLL) and a DC-chopper protection. A coordinated approach of improving the performance all the converter schemes with series dynamic braking resistor (SDBR) was analyzed. Investigation of the SDBR best location in the DFIG architecture considering the best switching signal was also carried out. Furthermore, a new control strategy of PLL for DFIG system was used in conjunction with all the schemes and SDBR. Simulations were carried out in Power System Computer Aided Design and Electromagnetic Transient Including DC (PSCAD/EMTDC). The results show that the SDBR can improve all the converter schemes during transient. Also, the DFIG-based variable speed wind turbine response during transient considering the 2-level single step IGBT converter could be further enhanced using the new proposed strategy.